Current status of the immunogenicity of enzyme replacement therapy in fabry disease - Jorge F. Gómez-Cerezo; Julián Fernández-Martín; Miguel Ángel Barba-Romero; Rosario Sánchez-Martínez; Alvaro Hermida-Ameijeiras; Maria Camprodon-Gómez; Saida Ortolano; Mónica A. Lopez-Rodriguez (Orphanet Journal of Rare Diseases)
Abstract In patients with Fabry disease (FD), treatment with enzyme replacement therapy (ERT), may trigger the formation of anti-drug antibodies (ADAs). The consequences of this immune reaction range from the transient appearance of clinically insignificant ADAs to the generation of neutralizing antibodies that negate the clinical benefit of the biotherapeutic agent, lead to side effects (such as injection site reactions), and even cause severe, life-threatening symptoms. Many factors may influence the immunogenicity of these therapeutic proteins. Currently, there are three commercially available long-term ERT treatments in patients with FD: agalsidase alfa, agalsidase beta, and more recently, pegunigalsidase alfa. Neutralizing ADAs are present in approximately 40% of male FD patients treated with ERT based on agalsidase alfa or agalsidase beta and have shown in vitro cross-reactivity with both agalsidases. Their formation seems to be irreversible, meaning that most patients with positive neutralizing ADAs remain so for up to 10 years after starting treatment. Recent studies show that in some patients, pre-existing ADAs against agalsidase alfa and agalsidase beta have lower affinity and lower inhibitory effects against pegunigalsidase alfa. Additionally, in clinical trials involving naïve patients, neutralizing antibodies were mostly transient, although further studies are needed to confirm these findings in clinical practice. The formation of ADAs is often associated with a worse clinical prognosis and a faster progression of the disease. Given the rapid progression of FD, measuring ADAs titers is essential to provide personalised treatment for each patient. This is why international recommendations highlight the importance of monitoring the existence of ADAs, their neutralising activity, and globotriaosylsphingosine (lyso-Gb3) levels in patients receiving ERT. However, several unresolved issues remain, such as the importance of ADAs levels (particularly neutralising ADAs), the standardisation of assay methods, the interpretation of results, and the implications of these findings for therapeutic strategies. Overcoming the development of ADAs is critical to improving treatment outcomes in patients with FD, different strategies have been explored to address this challenge. The present work aims to review latest developments related to all aspects mentioned above, while also analyzing the potential role of therapeutic innovations.